Microfluidic approaches to the study of angiogenesis and the microcirculation. (July 2017) - Akbari, Ehsan; Spychalski, Griffin B.; Song, Jonathan W.
Abstract: Microfluidic systems have emerged as a new class of perfusable in vitro culture models that have helped advance and refine our understanding of microvascular function. Cutting‐edge microfluidic models have successfully integrated principles from quantitative analysis of vascular function, in vitro flow chambers, microfabrication techniques, and 3D tissue scaffolds. Here, we review the evolution of microfluidic systems, namely their progression from 2D planar microchannel arrays to 3D microtissue analogs, and highlight their recent contributions in elucidating the role of biomolecular transport and fluid mechanical stimuli in controlling angiogenesis. Further advancement of microfluidic systems in recapitulating tissue‐level phenomena in vitro, controlling important physiochemical and biological parameters, and integrating cellular and molecular analysis will help further enhance their application within the microcirculation research community.